1991
DOI: 10.4327/jsnfs.44.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Barley on Development of Experimental Diabetes in Rats.

Abstract: We studied the effect of barley on blood glucose response in normal and diabetic rats. In the first experiment, when male Sprague-Dawley rats were fed diets containing corn starch, barley, brown rice and wheat bran for 64 days, they were administered streptozotocin (4mg/100g body weight) intraperitoneally and the corresponding diet was continued for 46 days. Glucose tolerance was suppressed in normal and diabetic rats fed the barley diet. The effect of barley was especially marked in the diabetic rats. Fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In another study, Bourdon et al (1999) reported that carbohydrate was more slowly absorbed from highfiber meals containing naturally high β-glucan or flour enriched βglucan due to lower plasma concentration of insulin. In two other studies, streptozotocin-induced diabetic rats were used as experimental animals (Ikegami et al 1991, Naismith et al 1991. Glucose tolerance was more significantly suppressed in diabetic than in normal rats (Ikegami et al 1991).…”
Section: Hypoglycemic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Bourdon et al (1999) reported that carbohydrate was more slowly absorbed from highfiber meals containing naturally high β-glucan or flour enriched βglucan due to lower plasma concentration of insulin. In two other studies, streptozotocin-induced diabetic rats were used as experimental animals (Ikegami et al 1991, Naismith et al 1991. Glucose tolerance was more significantly suppressed in diabetic than in normal rats (Ikegami et al 1991).…”
Section: Hypoglycemic Effectsmentioning
confidence: 99%
“…In two other studies, streptozotocin-induced diabetic rats were used as experimental animals (Ikegami et al 1991, Naismith et al 1991. Glucose tolerance was more significantly suppressed in diabetic than in normal rats (Ikegami et al 1991). Naismith et al (1991) reported significantly lower water intake and weight loss in diabetic rats given barley than in those given wheat.…”
Section: Hypoglycemic Effectsmentioning
confidence: 99%
“…Foods prepared from barley are useful for diabetic and high blood pressure patients. It is suggested that barley could be therapeutic diet for diabetic patient, a good diet for kidney patient and the referred diet after convalescence (Ikegami et al, 1991).…”
mentioning
confidence: 99%
“…It is also used in poultry feed industries. However, barley-made foods are very useful for diabetic, cardiac and high blood pressure patients (Ikegami et al, 1991). It is rich in β-glucans, niacins, etc., which are very effective in lowering blood cholesterol level (Hales, 1992).…”
Section: Introductionmentioning
confidence: 99%